2018
DOI: 10.1159/000493621
|View full text |Cite
|
Sign up to set email alerts
|

miR-216b Post-Transcriptionally Downregulates Oncogene KRAS and Inhibits Cell Proliferation and Invasion in Clear Cell Renal Cell Carcinoma

Abstract: Background/Aims: Increasing evidence has shown that miR-216b plays an important role in human cancer progression. However, little is known about the function of miR-216b in renal cell carcinoma. Methods: The expression levels of miR-216b in renal cell carcinoma tissues and cell lines were examined by qRT-PCR. The biological role of miR-216b in renal cell carcinoma proliferation and/or metastasis was examined in vitro and in vivo. The target of miR-216b was identified by a dual-luciferase reporter assay. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…miRNAs can act as oncomiRs or tumor suppressors in ccRCC [9][10][11]. However, the effects and molecular mechanisms of miR-671-5p in ccRCC progression have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs can act as oncomiRs or tumor suppressors in ccRCC [9][10][11]. However, the effects and molecular mechanisms of miR-671-5p in ccRCC progression have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also showed antitumor effects of amygdalin in renal cell carcinoma (RCC) which ranked the second in genitourinary tumors in China . Juengel et al exposed RCC cells A498, Caki‐1and KTC‐26 to amygdalin at a dose of 10 mg/mL for 24 hours or 48 hours and used untreated cells as control.…”
Section: Recent Updates In Research Of the Anti‐tumor Effect Of Amygdmentioning
confidence: 99%
“…A previous study demonstrated the close relationship between miR-216b and different types of human cancer such as breast cancer, cervical cancer and colorectal cancer (35). miR-216b inhibits proliferation and promotes apoptosis in pancreatic cancer and clear cell renal cell carcinoma by downregulating KRAS (36,37). In colorectal cancer, miR-216b suppresses tumors by activating the JAK2/STAT3 signaling pathway (38).…”
Section: Discussionmentioning
confidence: 98%